2023
DOI: 10.3390/admsci13010018
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Turnover Intentions in a Public Hospital: The Mediating Effect of Organisational Commitment and Moderating Effect by Activity Department

Abstract: This research aimed to study the effect of leadership (transformational and transactional) on turnover intentions and whether this relationship is mediated by organisational commitment and moderated by the department of activity. To this end, it was hypothesized that: (1) leadership has a negative and significant association with turnover intentions; (2) leadership has a positive and significant association with affective organisational commitment; (3) organisational commitment has a negative and significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 68 publications
2
3
0
Order By: Relevance
“…The strength of the effect was practically the same between the three generations. Once again, among the variables under study, the one that proved to be the best reducer of intentions to leave was affective commitment, in line with the results obtained in previous studies Martins et al 2023).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The strength of the effect was practically the same between the three generations. Once again, among the variables under study, the one that proved to be the best reducer of intentions to leave was affective commitment, in line with the results obtained in previous studies Martins et al 2023).…”
Section: Discussionsupporting
confidence: 88%
“…At a time when one of the biggest problems facing organizations is high employee turnover (Reiche 2008;Martins et al 2023), leading to substantial financial losses for organizations, as the loss of a highly competent employee will affect the organization's reputation, profitability, and performance (Kumar et al 2021;Kakar et al 2023), this study has confirmed that if an organization wants to retain its best employees, it must invest in developing their skills in order to boost their emotional commitment and reduce their intentions to leave (Koster et al 2011;Nguyen et al 2020;Rodrigues et al 2019). It was also concluded that, of all the development practices studied, individualized support acts as the greatest reducer of intentions to leave, results that are maintained when analyzing the effect by generation.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, among the variables under study, the one that proved to be the best reducer of intentions to leave was affective commitment, in line with the results obtained in previous studies Martins et al, 2023).…”
Section: Discussionsupporting
confidence: 88%
“…At a time when one of the biggest problems facing organizations is high employee turnover (Reiche, 2008;Martins et al, 2023), this study has confirmed that if an organization wants to retain its best employees, it must invest in developing their skills in order to boost their emotional commitment and reduce their intentions to leave (Koster et al, 2011;Nguyen et al, 2020;Rodrigues et al, 2019).…”
Section: Discussionmentioning
confidence: 62%
“…Research on workplace commitment dates back to the 1960s and has focused primarily on the concept of organizational commitment ( Cohen, 2011 ). Organizational commitment refers to a psychological state that binds the individual to the organization ( Martins et al, 2023 ). With the current workforce becoming increasingly complex and flexible, people can no longer assume that organizational commitment is the only or primary commitment in the workplace ( Cohen, 2011 ).…”
Section: Literaturementioning
confidence: 99%